Prospects of gas-petroleum potential of deep-lying Waulsortian carbonate bosses in the central part of the Dnieper-Donets depression - Lukin, A. E.; Gaphich, I.P.; Makogon, V. V.; Kholodnyh, A. B. (Reports of the National Academy of Sciences of Ukraine, 2016)
Tournaisian-Lower Visean reef-carbonate complexes are presented with Waulsortion facies in Western Europe and Northern America. They are differ radically from other global stages of reefcarbonate formation by the absence of typical "ecological reefs". They are dark-coloured (with heightened content of kerogen and microbiogenic pyrites) micrite limestones. Their biota are presented mainly by fragments of crinoids and also bryozoans and brachiopods. They are distinguished from typical reef-carbonate rocks by heightened tightness (low primordial porosity and practical absence of permeability) and increased strength properties. But as it has been demonstrated by the results of investigation of Waulsortion facies in the Dnieper-Donets aulacogene, they begin to take secondaryreservoirs properties and offer a substantial hydrocarbon potential at great depths.